A Study of Optical Sensor in Clinical applications - IR. Dr. Kazi Kutubuddin Sayyad Liyakat (International Journal of Optical Innovations & Research, 2025)
The escalating demand for precise, real-time, and minimally invasive diagnostic and monitoring tools in clinical practice has propelled the development of sophisticated sensor technologies. Among these, optical sensors have emerged as a cornerstone, leveraging the interaction of light with biological matter to translate molecular or cellular events into quantifiable signals. Their inherent advantages – including high sensitivity, specificity, rapid response times, non-ionizing nature, and potential for miniaturization – make them exceptionally well-suited for diverse clinical applications. This paper provides an overview of the fundamental principles underpinning optical sensing, followed by an exploration of their critical roles across various clinical domains: from continuous glucose monitoring and early cancer detection to pathogen identification and point-of-care diagnostics. By enabling unprecedented access to physiological and pathological information, optical sensors are fundamentally transforming patient care, offering pathways to earlier intervention, personalized medicine, and improved health outcomes. Optical sensors are offering medicine a unique opportunity to shift the paradigm from reactive intervention to proactive, non-invasive surveillance. By using the oldest messenger in the universe—light—to eavesdrop on the body’s deepest molecular secrets, we are moving toward an era where diagnosis is immediate, omnipresent, and ultimately, kinder. The light revolution is turning the clinical experience into a conversation, where the body illuminates its own pathway to health.
Keywords: Optical Sensor; Pulse oximeter; clinical applications; light; patient care